Legal Review of the Release of Notification of Summons at the Gresik District Court Class 1 A Based on Perma Number 7 Of 2022 - Liana, Liana; Nurroso, Nurroso; Naibaho, Syintia Rosa; Sarifudin, Sarifudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the legal aspects and practices of the implementation of the release of court summons and notifications at the Gresik Class 1A District Court based on Supreme Court Regulation (PERMA) Number 7 of 2022 concerning Electronic Case and Trial Administration (e-Court). The purpose of this study focuses on the implementation of the e-court system in facilitating electronic summons of litigants and more efficient, fast, and low-cost trial notifications as an implementation of the principles of simplicity, speed, and low-cost in the judicial process. The results of the study indicate that e-court is able to reduce administrative obstacles and expedite the summons and notification process without having to go through a physical summons by a bailiff, thereby increasing access and transparency in the judiciary. This study discusses two problem formulations: to what extent is the relevance and conformity of the provisions of PERMA Number 7 of 2022 with the principles of procedural law and the principles of simple, fast, and low-cost justice related to the use of electronic release of court summons (e-court)? and What are the legal consequences if there is an implementation of release of court summons and notifications that does not comply with the provisions of PERMA Number 7 of 2022? This research uses a normative approach. This research is conducted by examining current regulations and other legal sources. The approaches used in this research include the statute approach, the conceptual approach, and the case study approach.